Captação de órgãos em Sergipe e fatores associados à efetivação de potenciais doadores - Nogueira, Emília Cervino (2009)
A disproportion exists between the number of patients in wait list for transplant and the organ procurement, that it can be related to possible flaws in the potential donors identification. To estimate the number of potential organ donors in Sergipe; to characterize the potential donors; to determine the frequency of donation and to know the factors associated to the no donation. Quantitative, descriptive and retrospective study using data collected from the medical records of patients up to 65 years old dead for traumatic brain injury, cerebrovascular stroke and primary brain tumor in the years 2005 to 2007 in three hospitals of Aracaju. Of 766 medical records analyzed, 257 had suggestive registration of brain death, being 148 with the Term of Declaration filled out. Eighty five percent of the potential donors were at the Public Hospital A. The median age was 33 years; prevailing the male (71,6%), the victims of traumatic brain injury (59,5%), and that in Urgency Unit (35,8%) and Intensive Therapy Unit (34,5%). Half of them presented signs of brain death in the first two days of hospitalization. Sixteen (10,8%) potential donors completed all the exams of the protocol of brain death and 12 (8,1%) became effective donors, being the absence of the diagnosis of brain death the principal cause of no donation. The time between the first registration and the removal of the organs was inferior at 40 hours in 50% of the donors. The number of potential organ donors in Sergipe has been underestimated due to flaws in the diagnosis and in the notification, resulting in a low donation index. The rates of family refuse and irreversible cardiac arrest suggest the need of educational actions driven to the health professionals and the society in general.